Partially randomized patient preference trial: Comparative evaluation of fibromyalgia between acupuncture and cupping therapy (PRPP-FACT). (November 2020) - Cao, Hui-Juan; Zhang, Ya-Jing; Zhou, Li; Xie, Zhan-Guo; Zheng, Ru-Wen; Hu, Hui; Li, Xin-Lin; Liu, Jian-Ping
Abstract: Background: and purpose The aim of this study was to investigate the feasibility of applying a partially randomized patients' preference (PRPP) trial in the clinical evaluation of acupuncture versus cupping therapy for fibromyalgia. Materials and methods: The final study included 126 participants. Participants without a treatment modality preference were randomly assigned to either the cupping therapy group or the acupuncture group. Patients with strong preferences were assigned to their treatment modality of choice. Ashi points were used for treatment. Outcome measures were both qualitative (patient expectation and satisfaction) and quantitative (drop-out rate, pain intensity, quality of life, depression assessment). Results: The recruitment of the non-randomized participants was completed 8 months before the randomized participants were recruited. There was no statistical difference related to the grouping method in the adjusted drop-out rate, patient expectation, and satisfaction. Conclusion: The PRPP model is suitable for use in the clinical evaluation of non-pharmaceutical therapies. Highlights: The drop-out rate of non-randomized participants had no difference with those who were randomized allocated. Neither the patients' expectation nor the satisfactory showed statistical difference related to the grouping method. Both acupuncture and cupping made clinical meaningful reduction of pain intensity, and the effect was similar. Partially randomized patient preference trial may be suitable for evaluating traditional Chinese non-pharmaceutical therapy.